Population pharmacokinetics of methadone hydrochloride after a single intramuscular administration in adult Japanese sika deer (Cervus nippon nippon). (25th June 2014) - Scala, Christopher; Marsot, Amélie; Limoges, Marie‐Josée; Locatelli, Yann; Simon, Nicolas; Alvarez, Jean‐Claude
Abstract Objective To assess the population pharmacokinetics of methadone in deer. Study design Prospective non‐randomized experimental trial. Animals Twelve healthy adult sika deer (nine males and three females). Methods Deer received intramuscular administration of racemic methadone hydrochloride at 0.5 mg kg−1 or 1 mg kg−1. Plasma methadone and its metabolite 2‐Ethylidene‐1, 5‐Dimethyl‐3, 3‐Diphenyl‐Pyrolidine (EDDP) concentrations were determined by validated liquid chromatography coupled to tandem mass spectrometry methods, at times 0, 30 minutes, 1, 2, 3, 4, 5, 6, 8, 12 and 24 hours. Population pharmacokinetics analysis was undertaken using a non‐linear mixed effects modelling (NONMEM). Results A two‐compartment linear disposition model best described observed time‐concentration profiles of methadone and EDDP. Population parameter estimates of methadone were elimination clearance (17.3 L hour−1), metabolic clearance (34.6 L hour−1), volume of distribution of compartment 1 (216.0 L) and volume of distribution of compartment 2 (384.0 L). Population parameter estimates of EDDP were elimination clearance (121.0 L hour−1), volume of distribution of compartment 3 (1.08 L) and volume of distribution of compartment 4 (499.5 L). The total clearance and total volume of distribution of methadone and EDDP were 51.9 L hour−1, 121.0 L hour −1, 600.0 L and 500.6 L, respectively. The methadone terminal elimination half‐life was 8.19 hours. No adverse effects were observed after methadone administration. Conclusions and Clinical relevance Following intramuscular injection, methadone was characterized by a large total volume of distribution, high systemic clearance and intermediate terminal half‐life in sika deer.